Determinan Pengetahuan HIV/AIDS pada Siswa SMA Negeri 1 Kambera Kabupaten Sumba Timur Tahun 2024 - Maria Vertiany Zefanya Tulus; Marni, Marni; Mega O. L. Liufeto (Yayasan Literasi Sains Indonesia, 2024)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system, resulting in a decrease in the body's ability to fight infection and potentially causing AIDS. This study aims to analyze the determinants that influence knowledge about HIV/AIDS among students of SMA Negeri 1 Kambera, East Sumba Regency, in 2024. Given the increasing cases of HIV/AIDS in Indonesia, a good understanding among adolescents is essential for the prevention of this disease. This method uses quantitative research with a cross sectional approach. The sample consisted of 75 students with the sampling technique using stratified random sampling. The analysis in this study used univariate analysis and bivariate analysis by testing the chi square relationship. The questionnaires distributed included aspects of knowledge, information sources, social, and peer influence related to HIV/AIDS. The results showed a significant relationship between knowledge and information sources (p=0.000), social life (p=0.045), and peer support (p=0.0147). It can be concluded that the factors associated with low HIV/AIDS knowledge include lack of accurate sources of information, social life with minimal open dialog about health issues, and lack of support from peers. This study suggests the need for more effective educational interventions, including counseling programs and awareness campaigns.